Genetic Algorithm-Based SVC Capacity Optimization for Voltage Stability in 500 kV Systems - Winarno, Istiyo; Iradiratu Diah P K; Belly Yan Dewantara (Muhammadiyah University, Sidoarjo, 2026)
General Background: Voltage stability and reactive power management remain critical operational challenges in large-scale 500 kV transmission systems operating under high loading conditions. Specific Background: Static Var Compensators (SVCs) are widely applied to support voltage regulation; however, determining appropriate SVC capacity remains complex because inadequate sizing may reduce system performance and increase transmission losses. Knowledge Gap: Previous studies have frequently emphasized voltage improvement in simplified benchmark systems without comprehensively integrating realistic power flow simulation and transmission loss evaluation in large-scale networks. Aims: This study aims to determine the optimal SVC capacity using a Genetic Algorithm (GA) to improve voltage stability and reduce transmission losses in a 500 kV transmission system. Results: A quantitative simulation-based framework integrating ETAP load flow analysis and MATLAB-based GA optimization was implemented under steady-state operating conditions. The base-case scenario recorded a minimum voltage of 455.009 kV and total transmission losses of 607.32 MW. After applying optimized SVC capacities of 404.80 MVAr, 288.43 MVAr, and 175.94 MVAr at critical buses, voltage magnitudes increased by 0.98%–7.89%, while transmission losses decreased to 594.30 MW, representing a 13.02 MW reduction or 2.14% improvement. The convergence analysis confirmed stable optimization behavior within 100 generations. Novelty: The study introduces an integrated simulation–optimization framework combining ETAP and GA for practical SVC capacity determination in a realistic 500 kV transmission network. Implications: The findings provide a reproducible and practical reference for reactive power planning, voltage stability improvement, and transmission efficiency optimization in large-scale power systems.